2003
DOI: 10.1097/00126334-200304010-00008
|View full text |Cite
|
Sign up to set email alerts
|

HIV Knowledge and Risk Behaviors Among Pakistani and Afghani Drug Users in Quetta, Pakistan

Abstract: Situated on the Pakistan-Afghan border, Quetta is home to growing numbers of Afghan refugees. We studied HIV knowledge and risk behaviors among Pakistani and Afghani drug users between July 2001 and November 2001. Of 959 drug users, all were male and the majority used heroin. Most were Pakistani (84.8%), 14.9% were Afghani, and 0.3% were Iranian. Relative to Pakistani drug users, a higher proportion of Afghanis reported no formal education, homelessness, and unemployment ( p <.001). Afghanis were more likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 9 publications
1
63
1
Order By: Relevance
“…We have previously shown that, compared to Pakistani drug users in Quetta, Afghani drug users were more likely to have ever injected drugs and to have reported higher levels of needle sharing. 13 While the proportion of drug users who reported injecting drugs was relatively low during the study period, the war in Afghanistan that immediately followed interrupted the heroin supply from Afghanistan to Pakistan; this in turn could precipitate transitions to injection drug use. 2,3,14 Decreasing heroin purity or increasing price may also lead to increased injection drug use since this route of administration is more efficient than inhalation or smoking.…”
Section: Discussionmentioning
confidence: 96%
“…We have previously shown that, compared to Pakistani drug users in Quetta, Afghani drug users were more likely to have ever injected drugs and to have reported higher levels of needle sharing. 13 While the proportion of drug users who reported injecting drugs was relatively low during the study period, the war in Afghanistan that immediately followed interrupted the heroin supply from Afghanistan to Pakistan; this in turn could precipitate transitions to injection drug use. 2,3,14 Decreasing heroin purity or increasing price may also lead to increased injection drug use since this route of administration is more efficient than inhalation or smoking.…”
Section: Discussionmentioning
confidence: 96%
“…This finding is higher than that of the study conducted among Afghani and Pakistani drug-users in Quetta, Pakistan. 22 It may be due to the fact that the education system in those countries has been affected by two Janeiro, Brazil, and Kabul, Afghanistan. 23,24 It appears that a major gap in knowledge exists among drug-users about the means of transmitting/ acquiring HIV.…”
Section: Discussionmentioning
confidence: 99%
“…According to data from the Behavioral Risk Factor Surveillance System (BRFSS), individuals living in neighborhoods where HIV is more prevalent tend to be tested more frequently 19 , probably since they are more familiar with issues related to both the infection and the clinical syndrome 20 .…”
Section: Variablesmentioning
confidence: 99%
“…be done to avoid HIV infection or AIDS 24 . This limited knowledge along with fatalism and denial 25 can be expressed as less preoccupation with one's serostatus 20 .…”
Section: Variablesmentioning
confidence: 99%